Increasing students' information literacy and creative thinking in Islamic religious education learning through reading, questioning, and answering learning strategy - As-Tsauri, Muhammad Sufyan; Islamiati, Mia (Universitas Negeri Yogyakarta, 2024)
This research was conducted starting from the existence of supporting facilities in schools such as libraries, and discussion methods in learning to improve students' literacy and creative thinking, but the results were not as expected. This research uses a quantitative approach with mixed methods research methods in the form of experiments with a quasi-experimental nonequivalent control group design, namely research conducted by looking at the differences between the experimental group and the control group. Data collection techniques used are tests, questionnaires, interviews, observations, and documentation. The results of this study are: first, the implementation of the RQA learning strategy begins with finding information, making questions and answers, and discussing it in class. Second, the information literacy ability of class VII students in general from the 6 literacy indicators of the Big6 model is categorized as good. Third, the average creative thinking ability of students in the experimental class = 86.25 is higher than that in the control class = 74.38. Fourth, the RQA learning strategy has a significant effect on the literacy and creative thinking abilities of students by obtaining the results of 3 indicators in the very good category and 3 indicators in the good category of literacy ability and the Sig (2-tailed) value of 0.006, so that H1 is accepted.